THE USE OF INFLUENCERS AND TIKTOK'S RECOMMENDATION ALGORITHM ON PURCHASE DECISION AND ITS IMPLICATION ON E-LOYALTY OF TIKTOK SHOP USERS - Mona Syafriani; Dini Hidayah (Institut Bisnis dan Teknologi Pelita Indonesia, 2025)
The increasing use of digital platforms such as TikTok Shop has transformed consumer shopping behavior; however, few empirical studies have examined the roles of influencers and recommendation algorithms in shaping purchase decisions and online loyalty (e-loyalty). This study aims to analyze the influence of influencers and TikTok’s recommendation algorithm on users’ purchase decisions and e-loyalty. A quantitative research method was employed using a survey of 384 respondents selected through simple random sampling, and the data were analyzed using path analysis. The results reveal that both influencers and TikTok’s recommendation algorithm significantly affect purchase decisions, yet only the algorithm has a direct impact on e-loyalty. Purchase decisions were found to significantly mediate the relationship between both influencers and e-loyalty, as well as between the algorithm and e-loyalty. These findings suggest that user loyalty on TikTok Shop is more influenced by purchase experience than by mere exposure to influencers. The novelty of this research lies in its identification of the mediating role of purchase decisions in bridging the influence of influencers and recommendation algorithms on consumer e-loyalty within the TikTok Shop context an area that has been underexplored in prior literature. Peningkatan penggunaan platform digital seperti TikTok Shop telah mengubah pola belanja konsumen, namun belum banyak kajian yang secara empiris menelaah peran influencer dan algoritma rekomendasi dalam membentuk keputusan pembelian serta loyalitas daring (e-loyalty). Penelitian ini bertujuan untuk menganalisis pengaruh influencer dan algoritma rekomendasi TikTok terhadap keputusan pembelian dan e-loyalty pengguna. Metode penelitian yang digunakan adalah kuantitatif dengan pendekatan survei terhadap 384 responden yang dipilih melalui simple random sampling, dan data dianalisis menggunakan path analysis. Hasil penelitian menunjukkan bahwa baik influencer maupun algoritma rekomendasi TikTok berpengaruh signifikan terhadap keputusan pembelian, namun hanya algoritma yang berpengaruh langsung terhadap e-loyalty. Keputusan pembelian terbukti memediasi secara signifikan hubungan antara influencer dan e-loyalty, serta antara algoritma dan e-loyalty. Temuan ini menegaskan bahwa loyalitas pengguna TikTok Shop lebih dipengaruhi oleh pengalaman pembelian daripada oleh eksposur terhadap influencer semata. Kebaruan dari penelitian ini terletak pada identifikasi peran mediasi keputusan pembelian dalam menjembatani pengaruh variabel influencer dan algoritma rekomendasi terhadap e-loyalty konsumen dalam konteks TikTok Shop, yang belum banyak dikaji dalam literatur sebelumnya.